Teaming from three perspectives. Interviews with participatory action research participants. (Kairaranga, 2008)
Taking part in the autism spectrum disorder participatory action research (ASD PAR) project was a genuine team effort for the group of people supporting Rose, a primary school student with Asperger syndrome. The following excerpts are from interviews with some of Rose's team, This is a collaborative approach to telling the story of the team's collaborative effort. The voice of Rose's parents, the principal of the school she attended and the resource teacher: learningand behaviour (RTLB) who coordinated the project, are all heard here and offer readers some insights on teaming from three perspectives.